Diagnostic utility of ultrasonography for thoracic and abdominal bacterial and parasitic diseases in ruminants: a comprehensive overview - Tharwat, Mohamed; Tsuka, Takeshi (Frontiers in Veterinary Science, 2024)
This review article describes the roles of ultrasound in assessing thoracic and abdominal infectious diseases, mainly bacterial and parasitic ones that affect farm animals, including cattle, camels, sheep, and goats. Ultrasonography is a non-invasive imaging technique used to diagnose infectious diseases affecting the cardiovascular, respiratory, digestive, urinary, and hepatobiliary systems. In cases of thoracic and abdominal infections, ultrasound typically reveals abnormalities in echogenicity and echotexture, the presence of unusual artifacts, and mass formation exerting pressure on surrounding structures. Inflammatory and degenerative changes within the viscera can be identified ultrasonographically by comparing the echogenicity of affected areas with that of the surrounding normal parenchyma, such as in fascioliasis. Bacterial and parasitic infections often result in capsular mass lesions with anechoic contents, as observed in hydatid cysts and cysticercosis, or varying echogenic contents, as observed in liver abscesses. Effusions within the pericardium, pleura, and peritoneum are common ultrasonographic findings in infectious thoracic and abdominal diseases. However, these effusions' echogenicity does not always allow for clear differentiation between transudates and exudates. The routine use of ultrasonography in the evaluation of the chest and abdomen in affected or suspected ruminants is highly beneficial for detection, guiding therapeutic decisions, assessing prognosis, and aiding in the eradication of highly contagious diseases that cause significant economic losses.